Improvement on marital satisfaction by using quality approach - Rika Fatimah .P.L, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
If a product is tangible to be measured then satisfaction is intangible to be measured. It has no quality standard therefore satisfaction is different according to one to others. In other way, we may say that satisfaction has various approaches to represents its quality level. Therefore in this study, we provide new perspective to improve marital satisfaction by using customer satisfaction based approach. Using the new approach, we identify gap value between spouse’s level of importance and practice with respect to several marriage dimensions chosen in this paper. Then, we emphasize some actions need to be taken to improve the marital satisfaction with precisely and specifically addressed to the most dimension needed. The inappropriate efforts may give no significance result to the marital satisfaction. In this article, we assess the quality of marital satisfaction to three dimensions which are Marital Relationship, Marital Adjustment and Marital Intimacy. 1,213 questionnaires returned are distributed across West Malaysia. The result shows that marital relationship is the first priority since this dimension has the lowest level of satisfaction, followed by marital intimacy then marital adjustment as the third priority needs to be improved.